2004
DOI: 10.1136/bjo.2003.017731
|View full text |Cite
|
Sign up to set email alerts
|

Ocular surface epithelium induces expression of human mucosal lymphocyte antigen (HML-1) on peripheral blood lymphocytes

Abstract: Background/aims: Peripheral blood CD8+ lymphocytes that home to mucosal surfaces express the human mucosal lymphocyte antigen (HML-1). At mucosal surfaces, including the ocular surface, only intraepithelial CD8+ lymphocytes express HML-1. These lymphocytes are retained in the intraepithelial compartment by virtue of the interaction between HML-1 and its natural ligand, E-cadherin, which is expressed on epithelial cells. The purpose of this study was to determine whether ocular surface epithelial cells (ocular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
(15 reference statements)
2
7
1
Order By: Relevance
“…Studies on ocular surface disease such as ocular cicatricial pemphigoid have demonstrated that the ratio of CD8/HML-1 did not change, whereas in conjunctival carcinoma in situ, the ratio was decreased 3. This supports the suggestion that HML-1 is not induced on CD8+ T cells in inflammatory conditions, and its increase in neoplastic conditions of the epithelium is likely to be due to increased proliferation of IELs or due to induced expression by proliferating epithelial cells 23 24…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Studies on ocular surface disease such as ocular cicatricial pemphigoid have demonstrated that the ratio of CD8/HML-1 did not change, whereas in conjunctival carcinoma in situ, the ratio was decreased 3. This supports the suggestion that HML-1 is not induced on CD8+ T cells in inflammatory conditions, and its increase in neoplastic conditions of the epithelium is likely to be due to increased proliferation of IELs or due to induced expression by proliferating epithelial cells 23 24…”
Section: Discussionsupporting
confidence: 53%
“…HML-1 (CD103) is an αEβ7 integrin that binds to the ligand E-Cadherin, which is found on all epithelial layers of the conjunctiva and gut mucosa 7. Although HML-1 antigen is restricted primarily to IELs, its expression can be induced on T cells by exposure to various antigens and mitogens, and to cultured human corneal and conjunctival epithelial cells 23 24. In our study, the total percentage of CD3+ T cells that expressed HML-1 was low at around 8%.…”
Section: Discussionmentioning
confidence: 99%
“…Results from the present study may also suggest that among the circulating CD4 ϩ T cells, a dominant portion that naturally expresses the CD25 molecule is retained and survives in the conjunctival tissue by yet-to-be-defined mechanisms. It has also been shown that human conjunctival epithelial cells can induce the expression of human mucosal lymphocyte antigen 1 on CD4 ϩ T cells (31). These cells are retained in the intraepithelial compartment of the conjunctiva by virtue of the interaction between human mucosal lymphocyte antigen 1 and its natural ligand, E-cadherin, expressed on epithelial cells (31).…”
Section: Cd25mentioning
confidence: 99%
“…It has also been shown that human conjunctival epithelial cells can induce the expression of human mucosal lymphocyte antigen 1 on CD4 ϩ T cells (31). These cells are retained in the intraepithelial compartment of the conjunctiva by virtue of the interaction between human mucosal lymphocyte antigen 1 and its natural ligand, E-cadherin, expressed on epithelial cells (31). Suffia and coworkers recently showed a critical role for the ␣ E chain (CD103) of ␣ E ␤ 7 in the retention of CD4 ϩ CD25 ϩ T reg cells at mucocutaneous sites of inflammation (73).…”
Section: Cd25mentioning
confidence: 99%
“…Another observation suggesting E 7 integrin involvement in Treg activity is that CD8+ E 7 intraepithelial lymphocytes (IELs) home to the ocular surface by their interaction with E-cadherin, which is found in the conjunctival epithelium. These findings show that these integrins possibly have a localizational role in their interactions with Tregs [46,[141][142][143][144].…”
Section: Regulation Of Efferent Pathways and Cellular Effectors Of Admentioning
confidence: 91%